Time-Space Relations in the Concepts of Literary Thinking: a Review of Key Ideas - Vitalia Havrylenko-Rusak (Vasyl Stefanyk Precarpathian National University, 2022)
The article deals with key approaches to the definition of the "time" and "space" concepts both in the general scientific context and in philology in particular. It determines the factors forming the time-space coordinate system of a literary work as well as the factors influencing its realization in each specific text. The article provides the analysis of the peculiarities of the chronotope in the collection of poetic works of Serhii Zhadan "Life of Mary". It is determined that the time-space relation in the poetic texts of the collection is presented as a specific paradigm "home - non-home - anti-home". The chronotope of "home" finds its interpretation through the images of lost but one's own/native space. In turn, the chronotope of "non-home" is interpreted through the images of other people's apartments, cities, travel suitcases, while the chronotope of "anti-home" can be read through the images of death, an abandoned and dead city, a destroyed church, a grave.